Fascination moderates the effects of nature video exposure on creative thinking - Koivisto, Mika; Lahnalahti, Iida; Malmberg, Ida; Grassini, Simone (Academic Press, 2026)
Exposure to nature has been thought to facilitate creativity, but there exists only limited causal evidence to support such relationship. The present online experiment (n = 297) examined whether exposure to nature videos, as opposed to urban videos, enhances creative divergent thinking in verbal or visual modalities and whether the restorative components assumed by Attention Restoration Theory (being away, fascination, scope, coherence) or by Stress Reduction Theory (positive emotions, relaxation) mediate or moderate the effects of the exposure on verbal or visual divergent thinking. The responses' creative quality, originality, flexibility, and fluency were measured. Nature video enhanced the creativity and originality of verbal divergent thinking and the creativity of visual divergent thinking. No mediation effects were detected. However, of the restorative components, fascination was most clearly found to moderate the effects of video exposure on the originality of verbal and visual divergent thinking, suggesting that participants who were fascinated or inspired by nature benefited the most from nature exposure. The results support the positive impact of nature exposure on creative divergent thinking. Additionally, individual differences in the subjective experiences of nature appear to play a significant role in the beneficial effects of nature on creative thinking. The results encourage incorporating natural elements into built environments, such as workplaces and schools, where creativity is important.